Antibiotic Susceptibility Pattern of Bacterial Isolates from Infected Diabetic Foot Ulcer in Patients of Type 2 Diabetes Mellitus Presenting at Hayatabad Medical Complex Peshawar - Muhammad Sami; Sana; Usman, Khalid; Muhammad Muneeb (Indus Journal of Bioscience Research, 2024)
Objectives: This study aimed to determine the antibiotic resistance profiles of bacterial isolates obtained from diabetic foot ulcers (DFUs) in type 2 diabetes patients at Hayatabad Medical Complex, Peshawar, by identifying the most prevalent bacterial species and their corresponding resistance patterns. Materials and Methods: This cross-sectional study was conducted over six months from March to September 2024, involving 120 clinically diagnosed patients with infected diabetic foot ulcers. Bacterial isolates were obtained from wound swabs and identified using standard cultural and biochemical tests. Antibiotic susceptibility was determined through the disc diffusion method. Results: The results indicated that 93.3% of wound swabs showed positive bacterial growth, predominantly gram-negative bacteria, with Escherichia coli (28%) and Klebsiella pneumoniae (22%) being the most prevalent isolates. Polymicrobial infections were found in 18% of samples. Resistance rates were notably high for ampicillin (72%) and ciprofloxacin (55%), while carbapenems and piperacillin-tazobactam demonstrated higher sensitivity. Among gram-positive isolates, methicillin-resistant Staphylococcus aureus (MRSA) was detected in 60% of cases. Conclusion: The research underscores the significant prevalence of multidrug-resistant (MDR) bacteria in diabetic foot ulcers, emphasizing the critical need for innovative approaches to antibiotic treatment and robust infection control strategies.